2021
DOI: 10.3389/fnins.2021.636969
|View full text |Cite
|
Sign up to set email alerts
|

Mutant PRPF8 Causes Widespread Splicing Changes in Spliceosome Components in Retinitis Pigmentosa Patient iPSC-Derived RPE Cells

Abstract: Retinitis pigmentosa (RP) is a rare, progressive disease that affects photoreceptors and retinal pigment epithelial (RPE) cells with blindness as a final outcome. Despite high medical and social impact, there is currently no therapeutic options to slow down the progression of or cure the disease. The development of effective therapies was largely hindered by high genetic heterogeneity, inaccessible disease tissue, and unfaithful model organisms. The fact that components of ubiquitously expressed splicing facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…The different PRPF31 -mutated iPSCs generated in our study expressed pluripotent markers and presented classical properties of human pluripotent stem cells, indicating that mutations in the ubiquitous PRPF31 gene did not affect the reprogramming of the pluripotent state per se. Furthermore, we were able to generate RPE cells and pseudo-laminated retinal organoids from several iPSC lines carrying different PRPF31 mutations, confirming that the differentiation process is not impaired, as recently reported for different PRPF8 and PRPF31 iPSCs 29 , 30 , 48 .…”
Section: Discussionsupporting
confidence: 88%
“…The different PRPF31 -mutated iPSCs generated in our study expressed pluripotent markers and presented classical properties of human pluripotent stem cells, indicating that mutations in the ubiquitous PRPF31 gene did not affect the reprogramming of the pluripotent state per se. Furthermore, we were able to generate RPE cells and pseudo-laminated retinal organoids from several iPSC lines carrying different PRPF31 mutations, confirming that the differentiation process is not impaired, as recently reported for different PRPF8 and PRPF31 iPSCs 29 , 30 , 48 .…”
Section: Discussionsupporting
confidence: 88%
“…A heterozygous knock-in mouse model carrying the prpf31 p.A216P mutation displayed RPE pathological morphologies, including a drusen-like deposit, large lipofuscin accumulation and atrophy of basal infoldings [ 33 ]. However, intriguingly, it was reported that PRPF8 mutation caused widespread splicing changes but did not display distinctly abnormal behavior in patient iPSC-derived RPE cells [ 8 , 40 ]. Therefore, different member mutations from the PRPF family may lead to different effects on RPE.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-mRNA processing factors (PRPFs) are essential for the U4/U6/U5 tri-snRNP complex, playing a critical role in the splicing process. Mutations in PRPF genes linked to adRP have been identified, including PRPF3 , PRPF4 , PRPF6 , PRPF8 , PRPF31 , SNRNP200 and RP9 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in pre-mRNA processing factors (PRPFs) are the main cause of autosomal dominant RP related to the formation of the U4/U6.U5 tri-snRNP complex, a core spliceosome component [ 39 ]. For instance, RPE cells generated from iPSCs of an RP patient carrying the PRPF8 mutation showed widespread changes in alternative splicing events and dysregulated expression of genes involved in the splicing process and ribosome, indicating loss of spliceosome function [ 40 ]. In addition, ROs and RPE models from patient-specific iPSCs with the PRPF31 mutation showed impaired pre-mRNA splicing process as described by Baskin et al On the other hand, abnormal photoreceptor and RPE changes were also observed, including cell morphology, cilium structure, apical-basal polarity, and phagocytosis function of the photoreceptor outer segment (POS) [ 41 ].…”
Section: Application Of Patient-derived Organoids In Irdsmentioning
confidence: 99%